Living the revolution : Italian women's resistance and radicalism in New York City, 1880-1945 - Guglielmo, Jennifer, 1967- (Gender & American culture., 2010)
Guglielmo brings to life the Italian working-class women of New York and New Jersey who helped shape the vibrant radical political culture that expanded into the emerging industrial union movement. Tracing the activism of two generations of women who worked in the needle and textile trades, she explores the ways immigrant women and their American-born daughters drew on Italian traditions of protest to form new urban female networks of everyday resistance and political activism. And she shows how their commitment to revolutionary and transnational social movements diminished as they became whit.